Perspectivas de mães adolescentes sobre o acolhimento em casa lar - Souza, Gabriela Sabrina da Silva (2023)
Institutional care of children in Brazil occurs when there are no more resources or possibilities for the child or adolescent to remain in their family of origin and, as a result, there is a separation from family life as a way of guaranteeing their protection. Foster care at Casa Lar emerges as a proposal to satisfy personalized care and in small groups by caregivers that stimulate the development of affective relationships similar to the family environment. The present study aimed to analyze the experiences of adolescents in Young mother’s Casa Lar. Two young women participated, one newly welcomed and the other discharged, both primiparous. A remote interview was carried out through the google meets platform. The interviews were transcribed and a thematic analysis was carried out. The results showed that the adolescents' perspective of Casa Lar was considered positive, and that this institutional environment was configured as a space that promoted affection, security and care. It discusses the need for public policies that act in the prolonged institutionalization of children and adolescents in foster care, and measures that contribute to the constant training of professionals linked to the service.